RELIGION IN THE MIDST OF THE PLURALITY OF INDONESIAN SOCIETY - Damsuki Damsuki; Khamam Khosiin; Datu Muhammad Nasaruddin; Julita Lindriany (Jurnal Scientia, 2023)
The so-called "Party of Democracy" situation does not deserve to be called a party. Most political elites are willing to create noise in society for the sake of their martyrdom. Religion is the easiest political commodity to use in campaigns. This is also supported because most people are still too "baper" about issues in the name of religion. Thus, they are very easily consumed by issues and provoked. This attitude can then trigger cases of intolerance and violence against religious freedom. This study aims to determine religious sentiments in the plurality of Indonesian society. The research method is a descriptive qualitative approach to present a complete picture of the problem under study. Data collection by interviews, observations, documentation studies and data analysis techniques through data reduction and closure. This study’s results state that religious sentiments arise in humans caused of a lack of deep understanding of religious teachings, resulting in blind fanaticism, the subjectivity of views, and monopolizing the truth of religious teachings. As a result, this will impact the cracking of harmony in life between religious people.